PEMANFAATAN MESIN PENCETAK PELET SEBAGAI SOLUSI PENINGKATAN PRODUKSI PETERNAKAN AYAM MASYARAKAT DESA BENCAH KABUPATEN BANGKA SELATAN - Saparin Saparin; Eka Sari Wijianti (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Bangka Belitung, 2021)
Raising chickens is one way to improve the standard of living, especially for people living in rural areas. Raising chickens is no longer a difficult activity, but if it is not accompanied by science and technology, the increase in chicken farm production will be very slow. Through community service program conducted at this time, is to support the activities of the village community chicken farm Bencah South Bangka district by utilizing a chicken feed processor in the form of pellet printing machine. Chicken pellet making machine is given to two groups of partners in the village who already have a conventional chicken farm. Assistance on how to use the machine is done so that partners can increase the productivity of chicken livestock that are being cultivated.